Search for massive resonances decaying into WW, WZ or ZZ bosons in proton-proton collisions at s√=13 TeV - Sirunyan,AM; Tumasyan,A; Adam,W; Asilar,E; Bergauer,T; Brandstetter,J; Brondolin,E; Dragicevic,M; Eroe,J; Flechl,M; Friedl,M; Fruehwirth,R; et al. (JOURNAL OF HIGH ENERGY PHYSICS, 2017)
A search is presented for new massive resonances decaying to WW, WZ or ZZ bosons in νqq¯¯ and qq¯¯qq¯¯ final states. Results are based on data corresponding to an integrated luminosity of 2.3-2.7 fb−1 recorded in proton-proton collisions at s√=13 TeV with the CMS detector at the LHC. Decays of spin-1 and spin-2 resonances into two vector bosons are sought in the mass range 0.6-4.0 TeV. No significant excess over the standard model background is observed. Combining the results of the νqq¯¯ and qq¯¯qq¯¯ final states, cross section and mass exclusion limits are set for models that predict heavy spin-1 and spin-2 resonances. This is the first search for a narrow-width spin-2 resonance at s√=13 TeV.